CaMKII determines mitochondrial stress responses in heart - Joiner, Mei-ling A. (2012)
Myocardial cell death is initiated by excessive mitochondrial Ca(2+) entry, causing Ca(2+) overload, mitochondrial permeability transition pore (mPTP) opening and dissipation of the mitochondrial inner membrane potential (ΔΨm)(1,2). However, the signaling pathways that control mitochondrial Ca(2+) entry through the inner membrane mitochondrial Ca(2+) uniporter (MCU)(3–5) are not known. The multifunctional Ca(2+) and calmodulin-dependent protein kinase II (CaMKII) is activated in ischemia reperfusion (I/R), myocardial infarction (MI) and neurohumoral injury, common causes of myocardial death and heart failure, suggesting CaMKII could couple disease stress to mitochondrial injury. Here we show that CaMKII promotes mPTP opening and myocardial death by increasing MCU current (I(MCU)). Mitochondrial-targeted CaMKII inhibitory protein or cyclosporin A (CsA), an mPTP antagonist with clinical efficacy in I/R injury(6), equivalently prevent mPTP opening, ΔΨm deterioration and diminish mitochondrial disruption and programmed cell death in response to I/R injury. Mice with myocardial and mitochondrial-targeted CaMKII inhibition are resistant to I/R injury, MI and neurohumoral injury, suggesting pathological actions of CaMKII are substantially mediated by increasing I(MCU). Our findings identify CaMKII activity as a central mechanism for mitochondrial Ca(2+) entry and suggest mitochondrial-targeted CaMKII inhibition could prevent or reduce myocardial death and heart failure dysfunction in response to common experimental forms of pathophysiological stress.